THE INFLUENCE OF COVID-19 INFORMATION ON WHATSAPP SOCIAL MEDIA TOWARDS COMMUNITY ANXIETY LEVEL - Puji Lestari; Ikhsan Fauzi Adha; Titik Kusmantini; Yuli Chandrasari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Many people in the Sorogenen Village and Mitra Griya Asri Housing communities are concerned about the COVID-19 information spread via the WhatsApp group social media. The goal of this study was to see how exposure to COVID-19 information on WhatsApp affected anxiety levels in the hamlet and housing communities, as well as to look at how exposure to COVID-19 information on WhatsApp affected anxiety levels in the communities. The Uses and Gratification Theory, Information Exposure Theory, Anxiety Theory, and Individual Difference Theory are all investigated in this study. The quantitative research method was applied, with each sample area consisting of 100 participants. All of the ideas employed in this study were evaluated on the designated population, according to the findings. The findings of the hypothesis 1 test show that the greater the exposure to COVID-19 information on WhatsApp, the higher the residents of Sorogenen Padukuhan's anxiety level. Hypothesis 2 was tested, claiming that the higher the level of exposure to COVID-19 information on WhatsApp social media, the higher the level of anxiety among Mitra Griya Asri Housing residents; and hypothesis 3 was tested, claiming that there is a difference in the effect of COVID-19 information on the people of the communities, but no difference in the level of anxiety among these residents. This research provides scientific contributions in the form of indicators of critical thinking to strengthen active audiences on Uses and Gratification Theory and intensity indicators on Information Exposure Theory.